A Fixed Point Approach to Stabilities of Functional Equations in Intuitionistic Fuzzy Banach Spaces: P. Saha, T. K. Samanta, Pratap Mondal, B.S. Choudhuryr - Team, Support (Thai Journal of Mathematics, 2022)
In this paper we consider some functional equations for studyingtheir Hyers-Ulam-Rassias stability. This stability has been studied fora variety of mathematical structures. Our framework of discussion is in-tuitionistic fuzzy normed linear space. We consider both Archimedeanand non-Archimedean varieties of such spaces. The approach to thepresent problem is a fixed point approach, that is, we obtain our resultsby applications of an extension of the Banach contraction mapping principle generalized metric spaces where innite distances are allowable.